Application of Digital Image Correlation (DIC) in resonance machines for measuring fatigue crack growth (Fracture and Structural Integrity, 2014)
This paper presents a simple experimental procedure that greatly facilitates the use of digital imagecorrelation (DIC) techniques in fatigue test conducted in resonant testing machines, without the need of testinterruptions. This is possible due to the implementation of USB interface optical microscopes of very smalldimensions, so that they can be mounted on the specimen as a contact extensometer. Thus, the microscopesampleassembly oscillates at the resonance frequency of the test. This is how, although the resonant testingmachine is in motion, and although the specimen is subjected to fatigue, changing its dimensions according tothe applied load, the acquired image is completely static. This allows the evaluation of the plastic deformationsgenerated by the crack growth, avoiding the elastic ones. Preliminary results on monitoring cracks with thistechnique on flat specimens with cylindrical notches of 1050 aluminium alloy are also presented.
Keywords: Resonance Machines